COST EFFECTIVENESS ANALYSIS (CEA) PENGGUNAAN GOLONGAN OBAT NEUROPROTEKTAN CITICOLINE INJEKSI DAN PIRACETAM INJEKSI PADA PASIEN STROKE DI RSU IMELDA PEKERJA INDONESIA MEDAN - Sinaga, Alex; Anjani, Agni (Universitas Imelda Medan, 2022)
Stroke is disease or functional disorder of the brain in the form of nerve paralysis (neurological deficit) due to obstruction of blood flow to the brain. One of the therapies given to stroke patients is by giving neuroprotectant drugs, namely citicoline injection and piracetam injection. The purpose of this study was to determine the effectiveness of therapy and cost effectiveness of stroke patients' therapy between the use of alternative citicoline injection and injection piracetam in a pharmacoeconomic manner with a Cost Effectiveness approach in RSU Imelda Pekerja Indonesia Medan. This study uses a retrospective Cohort Study method. The sample of this study consisted of 44 patients, namely 22 patients treated with citicoline injection and 22 patients treated with piracetam injection. The results of this study were obtained from the comparison of ACER (Average Cost Effectiveness Ratio) and ICER (Incremental Cost Effectiveness Ratio) values. The ACER value of citicoline injection is Rp. 11.949.- less than the ACER value of piracetam Rp. 15.474.- so that the Cost Effective ACER value which has the lowest ACER value is citicoline injection. The ICER value of the comparison of citicoline injection and injection piracetam is Rp. -32.661.- . which means the ICER result is negative or getting smaller, it is considered more effective and cheaper, in accordance with quadrant II the plant's cost-effectiveness decreases so that the neuroprotectant drug class therapy with the most Cost Effectiveness of stroke patients in RSU Imelda Pekerja Indonesian Medan is citicoline injection.